THE INFLUENCE OF VOCABULARY ON ENGLISH FOR TOURISM - Kurniawan, Edy (SCIENTIA JOURNAL, 2017)
This study analyzes the influence of vocabulary on English for tourismand WhichEnglish for tourism vocabulariesinfluence focus on vocabulary and meaning had existed in thetourism dictionary or not exist yet. This study uses the descriptive qualitative method. Theresearch object is the influence of vocabulary on English for tourism. The researcher took thedata from the journals, the relevant books, news papers, magazines, commercial break ontelevisions, radios, advertising, brochures,movies, and the social media such as; Face book,Twitter, and Internet, interviewing the persons that working in tourismaspects, and temples,beaches, busy streets, restaurants, cafes, hotels, hostels, motels, airports, and mounts. The techniques for collecting data used were noting technique, separating technique, and transferringtechnique. The data analyzing techniques applied the comparative qualitative method.The resultsof the research are as follows: (1) many the influence of English for tourism vocabularies thatfound in each function, namely; English for entertainment, English for restaurants and cafes,English for travel sea, English for travel holiday, English for travel air, and English for travelland; (2) there are so many English vocabularies that influence on English for tourism languagewhich do not exist yet in the tourism language dictionaries from each function.